Risk factors associated with mortality due to intraoperative cardiac arrest at Hospital Nacional Guillermo Almenara Irigoyen, 2011-2015 - Rosas Marroquín, Victor Hugo (2019)
Introduction. The incidence and mortality of intraoperative cardiac arrest (PCI) are indicators of quality of care and efficiency in surgical centers. Objective. To determine the risk factors associated with mortality due to PCI in the Hospital Nacional Guillermo Almenara Irigoyen, Lima, Peru, during the years 2011 to 2015. Methods. An observational, descriptive and retrospective study of PCI occurred during the study period, where the relative risk was determined. Results. Between the years 2011 to 2015 there were 88 PCI out of a total of 74 096 surgeries performed; the incidence of PCI was 11,87 x 10 000 surgeries. Of the 88 PCI, 39 patients died (44,3%); the intraoperative mortality was 5,26 x 10 000 surgeries. The risk factors associated with mortality due to PCI were: CPR greater than 20 min